Telaah Kualitas Hidup Pasien Penyakit Kronik di Kalimantan Barat - Untari, Eka Kartika; Yuswar, Muhammad Akib; Rizkifani, Shoma (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: The long duration of chronic disease affecting the patient’s quality of life. Every disease including chronic disease has a different duration and prognosis. The instrument that being used in measuring the quality of life can be very important factor. Quality of life assessment has a benefit by evaluate the treatment of patients with chronic disease, moreover the good quality of life will also increase the patient's life expectancy. The purpose of this article are to describe and identify instruments that being used to measure quality of life patients with chronic disease in West Kalimantan.Methods: This study conduct to review the original research articles with the keywords